ON PHONOSTYLISTIC STUDY OF UNIVERSITY LECTURE - Amirova, E.L.; Matveyeva, N.A. (Kostanay State Pedagogical Institute, 2017)
The article discusses the features of phonostylistic approach to describing prosody of the sounding text. The focus of the article is on the prosodic characteristics of a university lecture as one of the genres of academic public speech. First of all, extralinguistic factors that determine the nature of prosodic variation in academic public speech are highlighted. Second of all, the stylistic heterogeneity of university lecture is described. The length of syntagms varies from short to super-long intonation groups between the pauses. Such variability of syntagm’s length observed in a university lecture is an indicator of the interpenetration of academic and conversational styles. The segments are characterized by the following tonal features: narrow tonal range, smooth middle and low descending terminal tones, smooth tone in pre-nuclear parts of syntagm, smooth terminal tone in repetitions, creating the effect of “stringing”. Another indicator of stylistic heterogeneity is the use of tone markers characteristic of the conversational style (low terminal descending tone), as well as change of speech tempo.
Keywords: phonostylistics; phonetic style; extralinguistic factors; prosodic characteristics; university lecture